Translating the financial statements of subsidiaries operating in Turkey : Current/ Purchasing power parity method - Dumlu, Tuba Durmaz (My University, 1995)
unknown
Keywords: Genel yönetim; MALİ TABLOLAR; Mali yönetim; MUHASEBE-; Organizasyon ve finansman